A method of asymptotic expansion of an m-parameter family of solutions for a quasilinear system of differential equations - Elnazarov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
By using the method of asymptotic expansion of an m-parameter family of solutions, we obtain the asymptotic expansion of solutions of a quasilinear system of differential equations.